PERBEDAAN HASIL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) MENGGUNAKAN MIND MAPPING DAN SUMMARIZES PADA KELAS XI IPA MAN 1 KOTA BENGKULU TAHUN AJARAN 2017/2018 - Alfia Novera Indah Esa Kasih; Amrul Bahar; Salastri Rohiat (University of Bengkulu, 2018)
This study aims to determine differences in ProblemBased learning (PBL) using mind mapping ( PBL-mind mapping) and summarizes (PBL –summarizes) on the subject of ionic equilibrium in saline solution. The type of research used is quasi experimental research with population class XI IPA in MAN 1 Kota Bengkulu 2017/2018 academic year which amounted to 152 people and samples taken from normal and homogenous population by random sampling technique so that got sample that is class XI IPA 1 (PBL -Mind Mapping) as an experiment 1 with 36 people and class XI IPA 2 (PBL-Summarizes) as an experiment 2 which is 38 people.Data obtained in the form of cognitive domain learning results obtained from test results in the form of pretest and post-test. Data analysis used were mean score, normality test, homogeneity test, and hypothesis / t test with significance value ? = 0.05 calculated with SPSS 16.0 for Windows. Student learning outcomes in this study seen from the value of difference between pretest and post-test values. The average of pretest and post-test difference of experimental class 1 and 2 students were 56.11 and 49.21 and t-test obtained t-count value is greater than t-table (2.088> 1.99).The results of the data show that there are significant differences between the experimental classes 1 and 2 and show that the result of learning PBL using mind mapping is better with KKM achievement of 83.4% than the result of learning PBL using summarizes with KKM exhaust amounted to 68.4%.